2022
DOI: 10.6007/ijarbss/v12-i2/12259
|View full text |Cite
|
Sign up to set email alerts
|

Learning Grammar Using a Card Game

Abstract: Learning grammar may be perceived as challenging and difficult by many ESL learners. One effective way to attract them to learn grammar is by incorporating games in the lessons. This study involves the use of a language card game titled 'Jester', which is inspired and adapted from Donkey and Joker games. The current study aims to examine university students' attitude towards Jester and how Jester helps them in learning Adjectives. The methodology comprises a mixed method research design using a questionnaire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…Both learner and teacher participants addressed this aspect, with learners expressing enjoyment of the card game activity and teachers anticipating their learners' enthusiasm while using the cards. This observation aligns with findings from previous studies, where learners reported higher levels of engagement towards gamebased learning (Muslichatun, 2013;Sung & Ching, 2012;Zakaria et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Both learner and teacher participants addressed this aspect, with learners expressing enjoyment of the card game activity and teachers anticipating their learners' enthusiasm while using the cards. This observation aligns with findings from previous studies, where learners reported higher levels of engagement towards gamebased learning (Muslichatun, 2013;Sung & Ching, 2012;Zakaria et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Insights from teacher participants further emphasized the potential of our card game for enhancing productive skills, with suggested activities aligning well with oral and written tasks. These findings lead us to conclude that card games, in addition to strengthening vocabulary and grammatical development (Razali et al, 2017;Sung & Ching, 2012;Zakaria et al, 2022), can also foster speaking and writing skills (Limantoro, 2018;Muslichatun, 2013;Zakaria et al, 2022). However, further research is necessary to explore the effectiveness of card games in fostering productive skills and to identify best practices for their implementation in educational settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation